Detection of facial changes for hospital ICU patients using neural network - Muhammad Naufal, Mansor; Sazali, Yaacob, Prof. Dr.; Ramachandran, Nagarajan, Prof. Dr.; Muthusamy, Hariharan (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/